BREAD FRUITS PUDDING DENGAN PEMANIS ALAMI SEBAGAI ALTERNATIF DESSERT UNTUK PASIEN DIABETES MELLITUS: Bread Fruits Pudding With Natural Sweeteners as An Alternative Dessert For Diabetes Mellitus Patients - Rosyda Dianah; Rayhan (IPB University, 2021)
ABSTRACTThe aim of this study is modify dessert for patients or people with diabetes mellitus in the form of Bread Fruit Pudding with natural sweeteners. Bread Fruit Pudding products use the main ingredients of jelly and low fat milk and fruit as a sweet taste. Pudding product development into bread fruit pudding is attempted to increase public insight regarding the importance of considering the use of sugar and changing the negative stigma of society regarding the consumption of fruit with a sweet taste. The production stage of Bread Fruits Pudding products consists of the preparation of materials and tools, the processing stage using the boiling technique (100˚C) and serving (150 grams/serving). The nutritional content of Bread Fruits Pudding is 92.7 Calories of energy; 5.3 grams of protein; 3.8 grams of fat; 12.9 grams of carbohydrates; 2.2 grams of fiber and 6.6 grams of natural sugar. The result of the preference test obtained that 78% liked the appearance and portion of the product, 56% liked the taste and 89% liked the texture. The composition of ingredients in pudding products in the community generally uses a lot of sugar or added artificial sweeteners that increase the risk of Diabetes Mellitus, Pudding product development into bread fruit pudding is efforts are made to become a solution for pudding products that are safe for consumption without any risk to health in consuming it.